Seroprevalance of hepatitis B Virus, human immunodeficiency virus and hepatitis C virus among blood donors: a retrospective study - Dr. Indrani N. Banasode; Dr. Ashraf A. Zubair (Tropical Journal of Pathology and Microbiology, 2019)
Background: Screening of life threatening transfusion-transmissible infections (TTIs), like Human Immunodeficiency Virus (HIV), Hepatitis B and Hepatitis C Virus (HBV and HCV) in blood donors is important to maintain transfusion safety.Objective: To determine the prevalence of HBV, HIV and HCV in blood donors in Blood Bank of our hospital. Material and Methods: A retrospective analysis of 37,090 blood donors’ records was carried out over a period of five years from 2010 to 2014.Results: Of the 37,090 donors, seroprevalence of HBV, HIV and HCV was 1.5%, 0.6% and 0.2% respectively.Conclusion: Transfusion Transmitted Infections (TTIs) are important consideration for safe blood transfusion. The precise estimate of prevalence of viral infections in a group will help to monitor transfusion safety measures.